Health-related behaviours and their relationship with self-rated health among Canadian adults - Natalie D. Riediger; Andrea E. Bombak; Adriana N. Mudryj (BMC, 2019)
Abstract Background Self-rated health (SRH) is a commonly used survey measure as a substitute for a clinical measure of health, which has demonstrated validity and reliability in a variety of populations. The referents that individuals incorporate into their self-evaluations have been shown to include health-related behaviours, though these relationships are not static. Our purpose was to describe and test for relationships between health-related behaviours and SRH among Canadian adults. Methods We used pooled data from the Canadian Health Measures Surveys Cycles 3 (2012-13) and 4 (2014-15). All men and non-pregnant women aged 18 years and older were included (n = 6,789). We used binary logistic regression to test for relationships between health-related behaviours and SRH, including smoking status, adequate fruit and vegetable intake, inadequate sleep, alcohol use, and adequate physical activity. Results The majority of respondents rated their health as good, very good, or excellent, though differences in SRH were found according to age group, highest level of household education, and income adequacy. Inadequate sleep was most strongly associated with poorer SRH among men and women combined, as compared to other health-related behaviours. Among women only, those who report heavy episodic drinking (OR, 2.64) or daily drinking (OR, 3.51) rated their health better, as compared to women who report low-risk alcohol use. Conclusions Sleep quality is an important predictor of SRH for both men and women. Second, sex/gender differences must be considered in strategies to address alcohol use, as we may not be fully appreciating potentially health-affirming qualities associated with alcohol use among women.